Examining the effect of Consumption Time of Different Levels of Restaurant Waste Rice on Blood Factors and Liver Enzymes in Lori Fattened Lambs - Mehdi Aali Joodaki (Journal of Global Pharma Technology, 2017)
To examine the effect of replacing time of different levels of restaurant rice waste with barely on blood parameters and liver enzymes in Lori fattened lambs was used forty heads of male lamb of strain of Lori with an average weight of 25 kg, randomly divided into 5 groups. Energy and protein diets were identical and determined based on 80% concentrate and 20% forage. Restaurant rice waste at a ratio of zero, 25 percent, 50 percent, 75 percent and 100 percent was replaced by barley in diets of lambs. Feed and water were Fed freely to livestock. Lambs adaptation period to the experimental diets for 15 days and fattening period for 75 days was considered. On the days 30, 60 and 90 of test were performed sampling through the jugular vein in the neck of lambs, and hematological parameters including glucose, cholesterol, triglyceride, HDL, LDL, VLDL and liver enzymes including alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase were measured. The results showed that the concentration of triglyceride and VLDL in blood serum and liver enzymes of alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase were significantly affected by different treatments (p<0.05). But treatments had no significant impact on the concentration of HDL, LDL, glucose and cholesterol in blood serum and liver enzyme of alkaline phosphatase in fattened lambs (p>0.05). Sampling time had no significant effect on the concentration of triglyceride and VLDL in blood serum and liver enzyme of alkaline phosphatase in fattened lambs (p>0.05), but made significant changes in the concentration of HDL, LDL, glucose and cholesterol in blood serum and liver enzymes of alanine aminotransferase and aspartate aminotransferase in fattened lambs (p<0.05). Generally, the results showed that can use restaurant waste rice in diet of fattened lambs, without having harmful effects.Keywords: Rice waste, Hematological/blood parameters, Liver enzymes, Fattened lambs.